2009
DOI: 10.1111/j.1471-1842.2008.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

A negative trend of biomedical research in Libya: a bibliometric study

Abstract: Background: It is well established that Libya is lagging behind its peers in biomedical research. The aim of this study is to analyse all the original biomedical publications affiliated with Libya from 1973 to 2007. Methods: PubMed and the Science Citation Index Expanded were searched for 'original research' biomedical studies affiliated with Libya. The generated data were hand searched and 329 'original research' studies were included in the analysis. Results: The first study was published in 1973. Publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…When comparing the dental faculty staff numbers and the oral health–related published research, Sebha University is far ahead of Benghazi University. Our search results are in complete agreement with Benamer et al (15, 39) who observed that Libya was lagging behind its peers in biomedical research publications and that the published scholarship of Libyan medical schools and, in our case, the Libyan dental schools, is extremely low and that only a few academic staff have a handful of publications listed in PubMed.…”
Section: Discussionsupporting
confidence: 92%
“…When comparing the dental faculty staff numbers and the oral health–related published research, Sebha University is far ahead of Benghazi University. Our search results are in complete agreement with Benamer et al (15, 39) who observed that Libya was lagging behind its peers in biomedical research publications and that the published scholarship of Libyan medical schools and, in our case, the Libyan dental schools, is extremely low and that only a few academic staff have a handful of publications listed in PubMed.…”
Section: Discussionsupporting
confidence: 92%
“…There are no research components in the curriculum resulting in students finishing their medical course without having been involved in any research project or even understanding the research concepts (Daw & Elkhammas 2008). This led to the lack of research culture among Libyan doctors, especially when the majority of expatriate doctors, who helped in establishing the medical schools, left the country (Benamer et al 2008). The culture of favouritism is rife when it comes to academic appointments and promotions within the medical schools (Daw & Elkhammas 2008).…”
Section: Research Activities and Biomedical Publicationsmentioning
confidence: 95%
“…Biomedical research papers in relation to the Libyan medical schools started to appear in the early 1970s, and peaked in 1988 by the publication of 23 original research articles. Unfortunately, the publications rate declined to eight in 2007 despite the dramatic increase in the number of the medical schools and incorporation of a research project as an essential requirement to obtain the Libyan Board from the LBMS (Benamer 2008).…”
Section: Research Activities and Biomedical Publicationsmentioning
confidence: 99%
“…3 Libya is an Arab and North African country with fast natural resources but has been documented with a very low biomedical research productivity among Arab and African nations. [4][5][6][7] Although many studies have investigated and analyzed the biomedical research productivity and trends from Libya, limited information is available on the oral and dentistry field or other professional medical disciplines. 8 Therefore the purpose of this brief study was to investigation the trends of biomedical publications productivity of oral and dentistry field from Libya using the most popular biomedical search engine PubMed with focus on Libyan academic institutions.…”
Section: Introductionmentioning
confidence: 99%